Pemberdayaan Masyarakat Nelayan Danau Singkarak melalui Pengembangan iIkan Bilih Asap - Delvi Yanti; Deivy Andhika Permata (Jurnal Pengabdian Warta Andalas, 2016)
One of the main results is the fish bilih Singkarak Lake. Fish Bilih (Mystacoleuseus padangensis) is a worldwide endemic fish found only in Singkarak Lake. Fish quickly experiencing a process of decay compared with other materials including fish bilih man. One way of preserving fish, among others, by way of fumigation. The objectives and specific targets are achieved on KKN-PPM activities: 1. obtain a method of curing fish bilih as a preservative as well as to add flavor and retain quality bilih fish. 2. The method of packing fish bilih obtain a unique, modern, durable, and varied and hygienic, and 3. obtain bilih smoked fish in attractive packaging. The method applied activities, can be reached through the approach to the fishermen to grow and increase the motivation for the development of the fish so that the smoke bilih KKN-PPM program is implemented well received. The activities carried out by the method of participative and action in the community of fishermen target group. KKN-PPM followed by 32 students. In this activity has created and delivered two units of smoked fish to a group of Petani Nelayan Pasir Singkarak (PNPS), and the inauguration of the central fish bilih Singkarak Like by subdistrict X Koto Singakarak which was also attended by the Chairman BPKKN Andalas University. This activity by students participating in KKN PPM together with partner groups (PNPS) and goverment Nagari Singkarak. Fish bilih result smoke in these activities has a water content of 9.08% fish skin that looks shiny.